Offset‐compensated and zero‐quantum suppressed ROESY provides accurate 1H–1H distances in small to medium‐sized molecules. (19th July 2016) - Boros, Sándor; Batta, Gyula
Abstract : A robust version of the off‐resonance ROESY pulse scheme is suggested for the measurement of proton–proton distances or slow chemical exchange in small to medium‐sized molecules. The method implements adiabatic ramps to establish a pair of opposite frequency off‐resonance spin lock fields – with optionally randomized duration – and adiabatic inversion pulses with simultaneous gradients for efficient zero‐quantum suppression. The amended pulse sequence yields pure absorption cross‐peaks and works safely for small to medium‐sized molecules. The applicability of the method has been demonstrated using small, rigid molecules (strychnine and codeine) and was also applied for a cyclic peptide and a small protein. We found that the pure phase cross‐peaks of the new ROESY version are beneficial for distance measurements. The one‐dimensional (selective) version of the new method is also powerful for measuring selected pair‐wise interactions and distance determination. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A robust version of the off‐resonance ROESY pulse scheme is suggested. The method implements adiabatic ramps to build up a pair of opposite frequency off‐resonance spin lock fields as well as adiabatic inversion pulses with simultaneous gradients for efficient zero‐quantum suppression. The applicability of the method is demonstrated using different sized model compounds. The selective 1D version of the method is also presented.